2013
DOI: 10.1155/2013/483145
|View full text |Cite
|
Sign up to set email alerts
|

The Role of “Mixed” Orexigenic and Anorexigenic Signals and Autoantibodies Reacting with Appetite-Regulating Neuropeptides and Peptides of the Adipose Tissue-Gut-Brain Axis: Relevance to Food Intake and Nutritional Status in Patients with Anorexia Nervosa and Bulimia Nervosa

Abstract: Eating disorders such as anorexia (AN) and bulimia nervosa (BN) are characterized by abnormal eating behavior. The essential aspect of AN is that the individual refuses to maintain a minimal normal body weight. The main features of BN are binge eating and inappropriate compensatory methods to prevent weight gain. The gut-brain-adipose tissue (AT) peptides and neutralizing autoantibodies play an important role in the regulation of eating behavior and growth hormone release. The mechanisms for controlling food i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 257 publications
(353 reference statements)
3
32
0
Order By: Relevance
“…There is evidence suggesting that anti-neuronal antibodies may be involved in the etiopathogenesis of autism, neuropsychiatric systemic lupus erythematosus, and multiple sclerosis (19,20). In addition, there has been an increase in the number of studies evaluating autoimmunity in the etiology of psychiatric diseases such as obsessive compulsive disorder, Tourette syndrome, and anorexia nervosa (13)(14)(15). Antibodies against glutamate NMDA receptors, GAD, and gliadin are closely related to CNS disorders (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence suggesting that anti-neuronal antibodies may be involved in the etiopathogenesis of autism, neuropsychiatric systemic lupus erythematosus, and multiple sclerosis (19,20). In addition, there has been an increase in the number of studies evaluating autoimmunity in the etiology of psychiatric diseases such as obsessive compulsive disorder, Tourette syndrome, and anorexia nervosa (13)(14)(15). Antibodies against glutamate NMDA receptors, GAD, and gliadin are closely related to CNS disorders (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that the auto-antibodies against glutamate N-Methyl-D-aspartate (NMDA) receptors, glutamic acid decarboxylase (GAD), and gliadin are closely related with central nerve system disorders (10)(11)(12). In addition, there is an increasing body of evidence indicating that the autoimmune mechanism may play a role in the etiology of ADHD similar to studies on the etiology of other psychiatric disorders, such as schizophrenia, obsessive compulsive disorder, and anorexia nervosa (13)(14)(15). In one study, it was proposed that anti-GAD65 auto-antibodies may be associated with ADHD (16).…”
Section: Introductionmentioning
confidence: 95%
“…In summary, the majority of these pharmacological agents did not show significant benefits in AN treatment but it is also not certain whether their potential is fully explored. Also not well understood and not well studied in human AN are neuropeptides and whether they can improve recovery [98]. …”
Section: Medication Studies In Anmentioning
confidence: 99%
“…Several genes that play an important role in appetite regulation and satiety are considered candidates and may be related to the development of ED [14][15][16][17][18] , but the results of these studies are still inconsistent 19,20 .…”
Section: Introductionmentioning
confidence: 99%